Decreased Norepinephrine Transporter Availability in Obesity: Positron Emission Tomography Imaging with (S,S)-[(11)C]O-Methylreboxetine - Li, Chiang-shan R. (2013)
OBJECTIVES: Noradrenergic dysfunction is implicated in obesity. The norepinephrine transporter (NET) regulates the synaptic availability of norepinephrine. However, NET availability has not been previously characterized in vivo in obese people using Positron Emission Tomography (PET) imaging. Here we report findings evaluating NET availability in individuals with obesity and matched lean (i.e., normal weight) comparison subjects. METHODS: Seventeen obese but otherwise healthy individuals with a mean±SD body mass index (BMI) of 34.7±2.6 and 17 lean individuals with a mean±SD BMI of 23.1±1.4 were studied using a High-Resolution Research Tomograph (HRRT) and (S,S)-[(11)C]O-methylreboxetine ([(11)C]-MRB), a radioligand selective for the NET. The regional brain NET binding potential (BP(ND)) was estimated by the multilinear reference tissue model 2 (MRTM2) with the occipital cortex as a reference region. BP(ND) for regions of interest were obtained with the Automated Anatomic Labeling (AAL) template registered to individual’s structural MR scans. RESULTS: Obese individuals had lower NET BP(ND) values in the thalamus (p<0.038, 27% reduction) including within the pulvinar (p<0.083, 30% reduction), but not in the hypothalamus, locus coeruleus or the raphe nuclei, compared to lean individuals. When age was included as a covariate, the difference in NET BP(ND) values remained significant in the thalamus (p<0.025) and pulvinar (p<0.042). CONCLUSIONS: These results indicate that NET availability is decreased in the thalamus, including the pulvinar, in obese individuals. These findings further support data indicating noradrenergic dysfunction in obesity and suggest impaired NE clearance in obesity.